Wheat genotypic variation in dynamic fluxes of WSC components in different stem segments under drought during grain filling - Zhang, Jingjuan; Chen, Wei; Dell, Bernard; Vergauwen, Rudy; Zhang, Xinmin; Mayer, Jorge; Van den Ende, Wim (Frontiers in Plant Science, 2015)
In wheat, stem water soluble carbohydrates (WSC), composed mainly of fructans, are the major carbon sources for grain filling during periods of decreasing photosynthesis or under drought stress after anthesis. Here, in a field drought experiment, WSC levels and associated enzyme activities were followed in different stem segments (peduncle, penultimate internode, lower parts of stem, and sheath) during grain filling. The focus was on two double haploid (DH) lines, DH 307 and DH 338, derived from a Westonia/Kauz cross, two drought-tolerant wheat varieties that follow different drought adaptation strategies during grain filling. The results showed that in irrigated plants, in the period between 20 to 30 days after anthesis (DAA), 70-80% of WSC were fructans. Before and after this period, the fructan proportion varied from 10 to 60%, depending on the location along the stem. Under drought, the fructan proportion changed, depending on genotype and developmental stages. After anthesis, stem fructans accumulation occurred mainly in the peduncle and penultimate internode until 14 DAA in both DH lines, with clear genotypic variation in subsequent fructan degradation under drought. In DH 307 a significant reduction of fructans with a concomitant increase in fructose levels occurred earlier in the lower parts of the stem and the sheath, as compared to DH 338 or other stem segments in both lines. This was associated with an earlier increase of grain weight and thousand grain weight in DH 307. Spatiotemporal analysis of fructan dynamics and enzymatic activities in fructan metabolism revealed that several types of FEHs are involved in fructan remobilization to the grain under drought.